The many faces of globular glial tauopathy: A clinical and imaging study. (1st November 2022) - Buciuc, Marina; Koga, Shunsuke; Pham, Nha Trang Thu; Duffy, Joseph R.; Knopman, David S.; Ali, Farwa; Boeve, Bradley F.; Graff‐Radford, Jon; Botha, Hugo; Lowe, Val J.; Nguyen, Aivi; Reichard, Ross R.; et al.
Abstract: Background: Globular glial tauopathy (GGT) has been associated with frontotemporal dementia syndromes; little is known about the clinical and imaging characteristics of GGT and how they differ from other non‐globular glial 4‐repeat tauopathies (N4GT) such as progressive supranuclear palsy (PSP) or corticobasal degeneration (CBD). Methods: For this case–control study the Mayo Clinic brain banks were queried for all cases with an autopsy‐confirmed diagnosis of GGT between 1 January 2011 and 31 October 2021. Fifty patients with N4GT (30 PSP, 20 CBD) were prospectively recruited and followed by the Neurodegenerative Research Group at Mayo Clinic, Minnesota. Magnetic resonance imaging was used to characterize patterns of gray/white matter atrophy, MR‐parkinsonism index, midbrain volume, and white matter hyperintensities. 18 F‐Fluorodeoxyglucose‐, 11 C Pittsburg compound‐, and 18 F‐flortaucipir‐positron emission tomography scans were reviewed. Results: Twelve patients with GGT were identified: 83% were women compared to 42% in NG4T ( p = 0.02) with median age at death 76.5 years (range: 55–87). The most frequent clinical features were eye movement abnormalities, parkinsonism, behavioral changes followed by pyramidal tract signs and motor speech abnormalities. Lower motor neuron involvement was present in 17% and distinguished GGT from NG4T ( p = 0.035). Primary progressive apraxia of speech was the most frequent initial diagnosis (25%); 50% had a Parkinson‐plus syndrome before death. Most GGT patients had asymmetric frontotemporal atrophy with matching hypometabolism. GGT patients had more gray matter atrophy in temporal lobes, normal MR‐parkinsonism index, and larger midbrain volumes. Conclusions: Female sex, lower motor neuron involvement in the context of a frontotemporal dementia syndrome, and asymmetric brain atrophy with preserved midbrain might be suggestive of underlying GGT.